Operationalization of Temporality of Future Professionals in the Field of Socionomics in the Dimensions of Psychological Well-being - Zavatskа , Nataliia; Petrenko , Maksym; Zavatskyi , Vadym; Zhyharenko , Ihor (Insight: the psychological dimensions of society, 2023)
The purpose of the research is to theoretically substantiate and empirically operationalize temporality of future professionals in the field of socionomics in the dimensions of psychological well-being. The purpose and hypothesis entail the following important tasks of the research: to find statistically significant differences of the research parameters between the samples of undergraduate students (seeking a Bachelor’s degree) and postgraduate students (seeking a Master’s degree); to establish statistically significant correlations of temporality with independent variables; to compare the samples of the respondents of an optimal profile (Group II) and the respondents of a general profile (Group I). Methods: theoretical – analysis, generalization and comparison; empirical – the questionnaire “Zimbardo Time Perspective Inventory” (ZTPI) (Zimbardo & Boyd, 1999), adapted by О. Senyk (2012); the questionnaire “The scales of psychological well-being” (SPW) (Ryff & Keyes, 1995) adapted by S. Karskanova (2011); the average score of the students’ academic performance was calculated using ECTS (a 100-point scale). Results. It was found that undergraduates (Group I) have a significant advantage only by one parameter – “future” (F) (U=612.000; p=.003). A correlation matrix was created. Ten significant correlations (р≤.05; р≤.01) of the parameters of time perspective with independent variables were registered. The total sample was divided into two groups: an optimal profile (Group 2) and a general profile (Group 1). An expected advantage of an optimal profile was registered by four scales: “life purpose” (t = 3.12; р < .010), “positive relationships” (t = 2.42; р < .050), “level of psychological well-being” (t = 2.21; р < .050) and “average score of academic performance” (t = 2.45; р < .050). Discussion and сonclusions. It was explained that a statistically significant advantage of the sample of undergraduates over the sample of postgraduates by the positive future (PF) (U=612.000; p>.010) is a high level of optimistic intentions in life perspective, a lack of negative or any other experience of practical activity and belief in one’s own success. It was substantiated that a life purpose in an optimal profile is a major dimension which has the highest level of a statistically significant difference (р < .010) in comparison with a general profile. It was generalized that operationalization of temporality of future professionals in the field of socionomics in the dimensions of psychological well-being possesses scientific novelty, and the obtained empirical data should be taken into consideration by organizers of educational process at universities.
Keywords: educational space, undergraduate, postgraduate, university, life perspective, time perspective, self-actualization